Mechanical properties and strengthening mechanism of SiCf/SiC mini-composites modified by SiC nanowires. Issue 2 (15th January 2021) - Wu, Pengfei; Liu, Yu; Xu, Shenwei; Fu, Zeyu; Pang, Aimin; Li, Wei; Yang, Haitang
Abstract: The effects of the SiC nanowires (SiCNWs) and PyC interface layers on the mechanical and anti-oxidation properties of SiC fiber (SiCf )/SiC composites were investigated. To achieve this, the PyC layer was coated on the SiCf using a chemical vapour infiltration (CVI) method. Then, SiCNWs were successfully coated on the surface of SiCf /PyC using the electrophoretic deposition method. Finally, a thin PyC layer was coated on the surface of SiCf /PyC/SiCNWs. Three mini-composites, SiCf /PyC/SiC, SiCf /PyC/SiCNWs/SiC, and SiCf /PyC/SiCNWs/PyC/SiC, were fabricated using the typical precursor infiltration and pyrolysis method. The morphologies of the samples were examined using scanning electron microscopy and energy dispersive X-ray spectrometry. Tensile and single-fibre push-out tests were carried out to investigate the mechanical performance and interfacial shear strength of the composites before and after oxidization at 1200 °C. The results revealed that the SiCf /PyC/SiCNWs/SiC composites showed the best mechanical and anti-oxidation performance among all the composites investigated. The strengthening and toughening is mainly achieved by SiCNWs optimization of the interfacial bonding strength of the composite and its own nano-toughening. On the basis of the results, the effects of SiCNWs on the oxidation process and retardation mechanism of the SiCf /SiC mini-composites were investigated.